2016
DOI: 10.1074/jbc.m116.755801
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Acid Sphingomyelinase-like Phosphodiesterase SMPDL3B Provides Insights into Determinants of Substrate Specificity

Abstract: Edited by Norma AllewellThe enzyme acid sphingomyelinase-like phosphodiesterase 3B (SMPDL3B) was shown to act as a negative regulator of innate immune signaling, affecting cellular lipid composition and membrane fluidity. Furthermore, several reports identified this enzyme as an off target of the therapeutic antibody rituximab, with implications in kidney disorders. However, structural information for this protein is lacking. Here we present the high resolution crystal structure of murine SMPDL3B, which reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…This, to date, little described protein is an enzymatic component of the lipid rafts of cell membranes and appears to be involved in a wide variety of molecular processes including the sphingomyelin metabolism [ 8 ]. Besides its relevance for membrane fluidity and lipid composition, SMPDL3B has been identified as a negative regulator of the innate immune signaling [ 14 ]. In addition, SMPDL3B overexpression reduces cell apoptosis and strengthens the actin skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, to date, little described protein is an enzymatic component of the lipid rafts of cell membranes and appears to be involved in a wide variety of molecular processes including the sphingomyelin metabolism [ 8 ]. Besides its relevance for membrane fluidity and lipid composition, SMPDL3B has been identified as a negative regulator of the innate immune signaling [ 14 ]. In addition, SMPDL3B overexpression reduces cell apoptosis and strengthens the actin skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, amino acid residues close to the active center of SMPDL3B have been identified. These can recognize endogenous molecules that modulate macrophage function [ 14 ]. Studies could show that decreased SMPDL3B levels lead to membrane disorder and a TLR-moderated hyperinflammatory cell phenotype [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…J o u r n a l P r e -p r o o f SMPDL3B is a glycosylphosphatidylinositol (GPI)-anchored membrane associated protein with homology to acid sphingomyelinase (ASMase) and involves in the sphingomyelin catabolic process 43 . It has been reported that SMPDL3B plays a role in podocyte injury from diabetic nephropathy or focal segmental glomerulosclerosis 44,45 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…SMPDL3b is a glycosylphosphatidylinositol (GPI)anchored protein [ 86 , 87 ] with reported roles in inflammatory processes [ 88 ] and in kidney diseases [ 6 , 40 , 85 ]. Recently, the crystal structure of murine SMPDL3b was revealed and helped to identify possible substrates for SMPDL3b, which included CDP-choline, ATP and ADP [ 89 ]. Sphingomyelin could also be a potential substrate for SMPDL3b.…”
Section: Sphingolipid Signaling In Glomerular Diseasementioning
confidence: 99%